The Effect of Schooling on Cognitive Skills - Carlsson, Magnus; Dahl, Gordon B.; Öckert, Björn; Rooth, Dan-Olof (The Review of Economics and Statistics, 2015)
To identify the causal effect of schooling on cognitive skills, we exploit conditionally random variation in the date Swedish males take a battery of cognitive tests in preparation for military service. We find an extra ten days of school instruction raises scores on crystallized intelligence tests (synonyms and technical comprehension tests) by approximately 1% of a standard deviation, whereas extra nonschool days have almost no effect. In contrast, test scores on fluid intelligence tests (spatial and logic tests) do not increase with additional days of schooling but do increase modestly with age.